Synergetic and innovative approaches to education (Revista de Investigaciones Universidad del Quindío, 2023)
A significant number of research results in different fields of knowledge are correlated by researchers with synergetics. The problems, content, research methods and results related to synergetics are characterized by ambiguous assessments and uncertainty. At the same time, synergetics as a scientific area of ​​research is in demand by society. The organic need of modern science for generalizing interdisciplinary research continues to stimulate the further development of synergetics and its emergence to a new level of integration interactions. Synergetics operates today as a category of scientific knowledge. The context of synergetics makes it possible for scientists of different specializations to interact fruitfully in the language of system understanding and the search for new solutions. The education system is one of the social subsystems of society.The modern socio-cultural space in which the education system functions is unusually rich in diverse content. Numerous social systems, traditionally existing and newly emerged, interact with each other, enter into certain relationships, and are in a state of constant activity. The combination of traditions and innovations is the main socio-cultural norm of relations between the old and the new, excluding their opposition and affirming their complementarity.
Keywords: synergetics; synergetic approach; pedagogy; education; multivariance; pedagogical technologies; interaction; cooperation